Optimizing Land Certificate Pawning Based On Sharia Principles As An Alternative Financing For The Community - Larasati Anyufa; Gneissa Beltsazar; Aleksander; Lastuti Abubakar (KRTHA BHAYANGKARA, 2024)
The practice of pawning in Indonesia, especially in the context of customary law, namely selling pawns, is often still used by the community today, but this practice is considered irrelevant along with the development of pawn practices in Indonesia. New regulations from PT Pegadaian (Persero) through pawning with pawn objects in the form of land in Sharia Pawnshops with the aim of providing financing for the community and to micro, small and medium enterprises and farmers who use productive land. The development of pawn practices in Indonesia is also marked by the existence of an online pawn mechanism that is rampant among the public today. On the other hand, online pawning is also considered to provide convenience for the pawn giver because it can be done anytime and anywhere and the pawn giver can also estimate for himself how much the value of the pawn object is, but of course on the other hand this online pawn also has several weaknesses. This research uses normative juridical research methods to describe problems and solutions in the context of the development of pawn practices in Indonesia and uses qualitative research methods and is balanced by conducting interviews with the Padasuka branch of Sharia Pawnshops, Bandung City.